(untitled) (ENTHYMEMA, 2016)
Il saggio esamina la figura della Lucia di Manzoni alla luce del ‘tipo’ letterario della ‘fanciulla perseguitata’, al crocevia fra agiografia, letteratura libertina, romanzo sentimentale, narrativa gotica e letteratura romantica. In particolare si sofferma, anche attraverso un’analisi comparata dei frontespizi de I promessi sposi e dell’edizione del 1791 di Justine, sulle affinità e le divergenze fra la Lucia di Manzoni e l’eroina di Sade, sostenendone la parentela intertestuale e la specularità, nell’essere entrambe risposte (solo apparentemente antitetiche) al problema metafisico del male. In questo senso si sottolinea l’influenza, su Manzoni e Sade, del modello mariano, nei decenni in cui si assiste, per reazione al laicismo illuminista e rivoluzionario, a un rinnovato culto per la Vergine, che culminerà con il dogma dell’Immacolata Concezione (1854) e le apparizioni di Lourdes (1858). The essay examines the figure of Manzoni’s Lucia in the light of the literary ‘type’ of the ‘persecuted maiden’, at the intersection between hagiography, libertine literature, sentimental novel, Gothic narrative, and Romantic literature. In particular, through a comparative analysis of the frontispieces of I promessi sposi and of the 1791 edition of Justine, it focuses on the similarities and differences between Manzoni’s Lucia and Sade’s eponymous heroine, arguing for an intertextual relationship between the two and suggesting their reciprocal specularity, in being both answers (only apparently antithetical) to the metaphysical problem of evil. From this angle, the essay analyzes the influence, on both Manzoni and Sade, of the figure of Mary, in the years witnessing – as a reaction against the secularization promoted by the Enlightenment and the French revolution – to a renewed worship for the Holy Virgin, later culminating in the promulgation of the Immaculate Conception dogma (1854) and the apparitions at Lourdes (1858).